Numerical Simulation of Flood Routing, Model of Dynamic Equations - Leo Hari Wiryanto; Ratna Widyawati (IndoMS, 2022)
Dynamic equations of flow in a rectangular inclined channel are solved numerically for the case where the friction force of the channel wall is neglected by the gravity force. The flow discharge and the cross-section area along the channel are physical quantity that is calculated. In non-dimensional variables, the equations indicate solution in traveling wave occurring for critical flow. Near that type of flow, the perturbation method is applied to get second order equations that are first order partial differential equation with external force from the lower order equations. Numerical solution is obtained by predictor-corrector method, and the effect of these second order equations can be observed to the traveling wave, depending on the type of the flow, su-percritical or subcritical.